Chemical and Metabolic Aspects of Antimetabolite Toxins Produced by Pseudomonas syringae Pathovars - Arrebola-Díez, Eva María; Cazorla-López, Francisco Manuel; Pérez-García, Alejandro; De-Vicente-Moreno, Antonio (MDPI, 2011)
Pseudomonas syringae is a phytopathogenic bacterium present in a wide variety of host plants where it causes diseases with economic impact. The symptoms produced by Pseudomonas syringae include chlorosis and necrosis of plant tissues, which are caused, in part, by antimetabolite toxins. This category of toxins, which includes tabtoxin, phaseolotoxin and mangotoxin, is produced by different pathovars of Pseudomonas syringae. These toxins are small peptidic molecules that target enzymes of amino acids’ biosynthetic pathways, inhibiting their activity and interfering in the general nitrogen metabolism. A general overview of the toxins’ chemistry, biosynthesis, activity, virulence and potential applications will be reviewed in this work.
Keywords: Pseudomonas syringae; Bacterias fitopatógenas; Fitotoxinas; Tabtoxin; Phaseolotoxin; Mangotoxin; Virulence; Arginine; Ornithine; Glutamine